TERAPI AUDIO UNTUK KEHAMILAN SEHAT (ATHP) GAMELAN KECIREBONAN MEMBANTU MENURUNKAN TEKANAN DARAH DAN MENINGKATKAN KUALITAS TIDUR PADA WANITA HAMIL DENGAN HIPERTENSI DI WILAYAH CIREBON - badriah62 badriah; Santi Wahyuni; Komarudin (PT Nuansa Fajar Cemerlang, 2026)
The Maternal Mortality Rate (MMR) is 359 per 100,000 live births. Pregnant women were said that hypertensive if their diastolic blood pressure was≥ 90 mmHg in 2 measurements; one hour apart or more. Antenatal care was very important for early detection that this pregnant woman is normal or has problems. Actions that are pharmacological and non-pharmacological. One of the complementary actions is the use of Audio Therapy Healthy Pregnancy (ATHP) in the Cirebonan gamelan. Background: The aim of this study is to find the effect of Audio Therapy Healthy Pregnancy (ATHP) Gamelan Kecirebonan on pregnant women with hypertension. Methods: Quasi experiment with one group pre-post test design and manufacture of ATHP Gamelan Kecirebonan had given listen thrity minutes. Population was pregnant women in the 2nd and 3rd trimester who experienced high blood pressure. Data analysis using the paired-t test. Total size of samples were 50 people. Results: ATHP of the tested music compositions is significantly better and feasible to be used as relaxation therapy, and is ready to be tested for its effect on changes in blood pressure in pregnant women with hypertension. It can be concluded that there is a significant difference in systolic pressure (p=0.000 < 0.05) and sleep quality (p=0.011 < 0.05) between before and after treatment in the case group. Conclusion: ATHP Gamelan Kecirebonan effective to reduce blood pressure and increase sleep quality after use regularly in pregnant woman with hypertension.